Increased cooperation between Slovenia and China over the past five years in the framework of the Initiative Belt - Raščan, Stanislav (Anali PAZU HD, 2022)
The Republic of Slovenia actively participated in the Platform 16 + 1 and in the Initiative Belt and Road from their establishment in 2012 (16+1) and 2013 (One Belt and One Road). As stated in the second paragraph of the Foreign Policy Strategy of the Republic of Slovenia, adopted in 2015, Slovenia wants in relation to Asia, to positioned itself in various initiatives through which our Asian partners have cooperated with Central and Souteastern Europe. In the article, we will prove the high position of Slovenia through the 16 + 1 Platform in the Belt and Road Initiative, based on historical, political, economic, local and personal cooperation between Slovenia and China.